CULTURAL FALSIFICATION THROUGH DOCUMENTARIES: THE CASE OF CLEOPATRA - abouelyazid, asmaa (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2025)
Cultural falsification has a direct and negative impact on collective consciousness and on the stereotypical image of peoples and communities in the perceptions and beliefs of other societies. Given the strong influence of visual media in shaping individuals' opinions and awareness, documentary films have an amplified effect, as they are often regarded as reliable sources of historical information. Therefore, any distortion or falsification in the information they present can have deep and lasting effects on the audience’s collective consciousness. This study examines the phenomenon of cultural falsification through visual media, with a focus on documentary films due to their significant role in shaping cultural awareness among viewers. The study analyzes the 2023 Netflix docudrama Queen Cleopatra, which stirred wide controversy upon its release for portraying Queen Cleopatra VII with dark African features, despite historical evidence affirming her Macedonian origin. The film is compared with another documentary titled Queen Cleopatra: The Search for the Truth, which features Egyptologist Dr. Zahi Hawass along with a number of other scholars.